2021
DOI: 10.1096/fj.202100819rrr
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional mitochondrial translation and combined oxidative phosphorylation deficiency in a mouse model of hepatoencephalopathy due to Gfm1 mutations

Abstract: Hepatoencephalopathy due to combined oxidative phosphorylation deficiency type 1 (COXPD1) is a recessive mitochondrial translation disorder caused by mutations in GFM1, a nuclear gene encoding mitochondrial elongation factor G1 (EFG1). Patients with COXPD1 typically present hepatoencephalopathy early after birth with rapid disease progression, and usually die within the first few weeks or years of life. We have generated two different mouse models: a Gfm1 knock‐in (KI) harboring the p.R671C missense mutation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Transcriptional markers of dysfunction and resulting damages were apparent at 20°C in northern Burntwood River sturgeon and were more extreme when compared to southern Winnipeg River sturgeon, highlighting potential population‐specific mitochondrial capacity. Additionally, a highly differentially expressed hub transcript ( gfm1 ) key to mitochondrial translation and oxidative phosphorylation (Berenguer et al, 2021) was altered as temperatures increased. Aside from the direct effects of decreased ATP production and increased reactive oxygen species damage, a decline in mitochondrial function also has implications for stress signalling, viral immune response and formation of heme as well as iron cluster assemblies required for oxygen transport and numerous cellular processes (Aijoka et al, 2006; Braymer et al, 2021; Hernansanz‐Agustin et al, 2020; Karnkokowska et al, 2016; Lin et al, 2006; Qin et al, 2010; Tovar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional markers of dysfunction and resulting damages were apparent at 20°C in northern Burntwood River sturgeon and were more extreme when compared to southern Winnipeg River sturgeon, highlighting potential population‐specific mitochondrial capacity. Additionally, a highly differentially expressed hub transcript ( gfm1 ) key to mitochondrial translation and oxidative phosphorylation (Berenguer et al, 2021) was altered as temperatures increased. Aside from the direct effects of decreased ATP production and increased reactive oxygen species damage, a decline in mitochondrial function also has implications for stress signalling, viral immune response and formation of heme as well as iron cluster assemblies required for oxygen transport and numerous cellular processes (Aijoka et al, 2006; Braymer et al, 2021; Hernansanz‐Agustin et al, 2020; Karnkokowska et al, 2016; Lin et al, 2006; Qin et al, 2010; Tovar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of glutamic acid is taken up by neurons, disturbing the neurotransmitter balance, and thus inducing neuronal dysfunction. It has been suggested that mitochondrial dysfunction in neurons, caused by altered neurotransmission alone, may lead to neuronal atrophy [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a patient with a mutation in the corresponding domain of TSFM, presented with infantile encephalocardiomyopathy and sensorineural hearing loss [ 130 ], thereby indicating that even disruption to the same interaction site can lead to distinct disease presentations, consistent with the heterogeneity typically observed in mitochondrial diseases. To explore these complex human disease presentations, a pathogenic variant, R671C, was introduced into the Gfm1 gene in mice, and found to cause a significantly milder disease than that observed in patients [ 131 ]. The reason for this was unclear, because residue R671 in both the human and mouse GFM1 protein is essential for its stability and weakens its interaction with the ribosome.…”
Section: Modeling the Role Of Mitochondrial Translation Factors In Di...mentioning
confidence: 99%
“…The reason for this was unclear, because residue R671 in both the human and mouse GFM1 protein is essential for its stability and weakens its interaction with the ribosome. While patients developed hepatoencephalopathy, the mutant mice displayed only a mild molecular phenotype in the liver, including significant decrease in Complex IV activity and a decreased translation rate [ 131 ]. In patients with fatal hepatopathy due to a GFM1 mutation, OXPHOS dysfunction appeared to correlate with residual protein abundance, which was absent in the liver, but maintained at 60% of control in heart, therefore maintaining sufficient translation capacity in this tissue [ 132 ].…”
Section: Modeling the Role Of Mitochondrial Translation Factors In Di...mentioning
confidence: 99%